APPLICATION OF DISCOVERY LEARNING MODELS TO IMPROVE STUDENTS 'INDONESIAN LEARNING ACTIVITY AND ACHIEVEMENT KELAS VII SMP NEGERI 2 LAHAT - Andi Irawan; Turdjai Turdjai (UNIB Press, 2019)
This researcher aims to describe the application of the Discovery Learning Model in increasing the Indonesian Language Learning Activities of Class VII Students. I at SMP Negeri 2 Lahat, describes the application of the Discovery Learning Model in improving the Indonesian Language Learning Achievement of Class VII Students. I at SMP Negeri 2 Lahat. Research conducted on classroom action combined with quasi-experimental. The subjects of this study were students VII A and B SMP N 2 Lahat as the PTK class and the experimental class while the VII A class was the control class. The instruments used were the observation sheet and the test. The data analysis technique used the formula for the average percentage value of classical learning completeness and the t test, while the observation data were analyzed with the highest average score, the lowest score, the difference in scores and the range of values for each criterion. The results showed that the application of the Discovery Learning model approach can increase student activity and learning achievement